Quantum chromodynamics - Greiner, Walter, 1935- (Springer-Verlag, 1995)
This is a selfcontained introduction to perturbative and nonperturbative quantum chromodynamics. Relativistic quantum field theory is recapitulated and scattering theory is discussed in the framework of scalar quantum electrodynamics. Then the gauge theory of quarks and gluons is introduced, before moving on to an advanced discussion of perturbative and nonperturbative techniques in state-of-the-art QCD.